An investigation of adoption behaviour for social commerce in the Kingdom of Saudi Arabia - Dhahery, Muhammad A. M. (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Social media has made a profound impact on the way goods and services are traded through online platforms. This new phenomenon has shifted power from sellers to the community of buyers, who rely on testimonies of other consumers prior to engaging in s-commerce transactions. Despite the buzz created by this virtual marketplace phenomenon, in countries such as Saudi Arabia, the growth of s-commerce usage is lagging behind the growth of Internet and mobile device users. The extant literature indicates that there is a dearth of sufficient empirical studies that present a nuanced understanding of the most significant external variables that influence behaviroal intentions of users of s-commerce. Based on research gaps identified in this study, a conceptual framework was developed by leveraging support from the technology acceptance model (TAM). This framework posits that six factors: Trust (TR), Perceived Usefulness (PU), Recommendations and Referrals (RR), Website Quality (WQ), Perceived Risk (PR), and Social Pressure (SP) come together to infleunce behavioral intentions of s-commerce users. To test the hypotheses, survey data was collected from 411 respondents that are s-commerce users in various regions of Saudi Arabia. The data were analyzed using AMOS (v.23). The results revealed that trust (β = 0.450, p<0.000), perceived usefulness (β = 0.273, p<0.000), and social pressure (β = 0.249, p<0.000), have a direct and positive relationship with behavioral intention. While, recommendations and referrals (β = 0.214, p = 0.002), and website quality (β = 0.530, p<0.000), have a positive relationship with trust. Finally, perceived risk (β = -0.096, p = 0.028) was found to have a negative relationship with trust.